Immunity Rights Problems before the ICC: Between the 1961 Vienna Convention and the 1998 Rome Statute - Sandy Kurnia Christmas; Kholis Roisah (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: The right to immunity in international law is a privilege granted to Diplomatic Officers in the context of carrying out missions, in particular, representing the state. The immunity rights of a Diplomatic Officer must be protected and respected by the recipient state as an obligation in diplomatic relations. The rights of immunity respected in customary international law under the 1961 Vienna Convention are inversely proportional to those stipulated in the 1998 Rome Statute regarding the abolition of immunity rights before the International Criminal Court. This thing then raises the status of immunity rights problems between the 1961 Vienna Convention and the 1998 Rome Statute of the International Criminal Court.Purpose/Objective Study: This study aims to examine the problematics of applying immunity rights for diplomatic officials, namely how the respect and protection of immunity rights regulated in the 1961 Vienna Convention and how the abolition of immunity rights held in the 1998 Rome Statute of ICC. This thing then looks for problems in immunity rights between the two conventions in practice and occurred-cases.Design/Methodology/Approach: This study used a normative research method. The assessment is carried out using a conceptual approach, a statute approach, and a case approach so that the relevance between the problem and the final purpose of this research is found.Findings: This study found several reasons regarding the status of immunity rights before the International Criminal Court, which raises the problem of weaknesses in international law related to immunity rights. The flaw was triggered due to the lack of legal certainty associated with the lack of hierarchy used in the provisions of international law. So that between the 1998 Rome Statute of ICC and the 1961 Vienna Convention, there was a dilemma in its application. Based on the case, the UN Security Council, as an international institution, influences the decision on how the status of the right to immunity can be applied or not.Paper Type: Research Article